2021
DOI: 10.1155/2021/8825970
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Functional Properties, and Resistant Starch of Freshwater Macrophytes

Abstract: Several aquatic macrophytes such as Colocasia esculenta, Eleocharis dulcis, Nelumbo nucifera, Sagittaria sagittifolia, Trapa bispinosa, and Typha angustifolia possessed carbohydrate mainly in their storage and reproductive parts. Starch morphology, total starch, and amylose content of these six freshwater plant species were determined. Their functional properties, i.e., starch crystallinity, thermal properties, and rheological behaviour were assessed. Large starch granules were in N. nucifera rhizome (>15 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
7
1
Order By: Relevance
“…[44][45][46] Resistant starch (RS) content in some EDCSs was found to reach 374 g kg −1 , similar to that of S. trifolia tuber, and higher than that of Trapa bispinosa seed, Colocasia esculenta corm and Typha angustifolia pollen. 45 RS is well known to elicit diverse beneficial effects, particularly on gut microbiota, diabetes and obesity. 47 Relatively higher RS content is more likely to make EDCSs promising raw materials for making functional foods and pharmaceutical excipients.…”
Section: Starchesmentioning
confidence: 99%
See 2 more Smart Citations
“…[44][45][46] Resistant starch (RS) content in some EDCSs was found to reach 374 g kg −1 , similar to that of S. trifolia tuber, and higher than that of Trapa bispinosa seed, Colocasia esculenta corm and Typha angustifolia pollen. 45 RS is well known to elicit diverse beneficial effects, particularly on gut microbiota, diabetes and obesity. 47 Relatively higher RS content is more likely to make EDCSs promising raw materials for making functional foods and pharmaceutical excipients.…”
Section: Starchesmentioning
confidence: 99%
“…EDCSs are C A ‐type starches with strong peaks at 2 θ ≈ 17° and 18° and possess high swelling power and pasting viscosity, but with relatively lower enthalpy and gelatinization temperature 43,44 . Amylose content of EDCSs ranges from 115 to 292 g kg −1 and contributes to the higher swelling power (SP); this is because the SP of starches relies on the free intra‐ and extracellular space, and amylose can disturb the lamellar organization in starches to enlarge the space, thereby facilitating water invasion 44‐46 . Resistant starch (RS) content in some EDCSs was found to reach 374 g kg −1 , similar to that of S. trifolia tuber, and higher than that of Trapa bispinosa seed, Colocasia esculenta corm and Typha angustifolia pollen 45 .…”
Section: Nutrients and Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also showed solid-gel characteristics and dynamic rheological properties [5]. In other research, water caltrop also showed a great amount of resistant starch and a number of nutritional benefits; hence, water caltrops have been cultivated for years as food or traditional medicine in India and China [6,7].…”
Section: Introductionmentioning
confidence: 95%
“…Lotus seed and rhizome can produce a large amount of starch unlike other crops that only have a single starch accumulating part (Guo, 2009). The starch properties of lotus seeds and rhizomes differ in physical structure and composition (Syed et al., 2021). A comparison of physicochemical properties of starches from seeds and rhizomes of lotus found that the morphologies, sizes, amylose contents, crystal properties, thermal properties, swelling powers, and hydrolysis properties were different (Man et al., 2012; Fan Zhu, 2017).…”
Section: Introductionmentioning
confidence: 99%